2016
DOI: 10.9734/ijpss/2016/26447
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Jelly Seed Disorder in ‘Tommy Atkins’ and ‘Van Dyke’ Mangoes as Affected by Agro-Ecological Conditions in Kenya

Abstract: Jelly seed disorder is one of the major problems in mango production in Kenya as well as other mango producing countries in the world. This problem manifests itself through breakdown of tissues around the seed of the affected fruits resulting in unmarketable fruits. Although the exact cause of jelly seed in mango is unknown, some reports indicate that the condition could be due to imbalance related to Ca, Mg, N and K supply to the fruit. To establish the extent of this problem in Kenya, a study was conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…The increase in the yield by application of calcium could be attributed to the role of calcium in cell formation and its prevention of cellular degeneration [5,6] Calcium is an important mineral in the formation of cell membrane and development hence increases in the fruit physical attributes. This was in agreement with previous studies as reported by [7,16,17,18,19,20,21]. These results are contradictory to those reported by [11,22] who reported no increase in weight and yield of fruits by application of calcium.…”
Section: Yield Parameterssupporting
confidence: 89%
See 4 more Smart Citations
“…The increase in the yield by application of calcium could be attributed to the role of calcium in cell formation and its prevention of cellular degeneration [5,6] Calcium is an important mineral in the formation of cell membrane and development hence increases in the fruit physical attributes. This was in agreement with previous studies as reported by [7,16,17,18,19,20,21]. These results are contradictory to those reported by [11,22] who reported no increase in weight and yield of fruits by application of calcium.…”
Section: Yield Parameterssupporting
confidence: 89%
“…This study was conducted in fruiting seasons 2017 and 2018 at Karurumo orchard Embu County, Kenya. The area has an elevation of 1174 m asl of coordinates 0° 32́ S 37°41 E [7] classified as lower midland 3 (LM3). This area receives an annual rainfall of 1206 mm, with a bimodal pattern and an average annual temperature of 22.7°C.…”
Section: Experimental Site Descriptionmentioning
confidence: 99%
See 3 more Smart Citations